Endobronchial ultrasound transbronchial needle aspiration in elderly patients: safety and performance outcomes EBUS-TBNA in elderly. (4th December 2020) - Olgun Yıldızeli, Şehnaz; Tufan, Aslı; Bozkurtlar, Emine; Arıkan, Hüseyin; Kocakaya, Derya; Eryüksel, Emel; Ceyhan, Berrin; Karakurt, Sait
Abstract: Aim: Complication rates are low and endobronchial ultrasound guided needle aspiration (EBUS-TBNA) is generally regarded as a safe procedure, but there is a very limited number of studies evaluating the efficacy and safety of the procedure in advanced ages. The aim of this study is to assess the safety and performance outcomes of EBUS-TBNA in elderly. Methods: It was a retrospective observational study; patients who received EBUS-TBNA between September 2016 and January 2018 were evaluated. We analyzed patient's characteristics, doses of midazolam, and lidocaine used, regions of lymph node biopsies, and complications. Also, functionality and general physical status of patients over 65 years of age were evaluated. Results: During study period 132 cases of EBUS-TBNA were evaluated. 39 (29.5%) cases were aged 70 years, and over. There were more comorbidities in older group. Performance status of older group was worse. Furthermore, when evaluated according to American College of Cardiology (ACC)/American Heart Association (AHA) and American Society of Anesthesiologists (ASA), the older group was found to be composed of the riskier patients. When patients aged between 65 and 69, and over 70 compared, older patient's Barthel, EQ 5-D, SGA, and G8 scores were found to be worse. Despite that, there was no difference in the frequency, and types of complications between both groups. Diagnostic performance was not different between age groups. Conclusions: Independent from comorbidities, general health status, and functionality EBUS-TBNA procedure in 70-year-old and over patients is a safe minimally invasive procedure.